2022
DOI: 10.1186/s12938-022-01006-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of the femoral neck system versus InterTan nail and three cannulated screws for unstable Pauwels type III femoral neck fracture

Abstract: Background There are a variety of internal fixation methods for unstable femoral neck fractures (FNFs), but the best method is still unclear. Femoral neck system (FNS) is a dynamic angular stabilization system with cross screws, and is a new internal fixation implant designed for minimally invasive fixation of FNFs. In this study, we conducted a biomechanical comparison of FNS, InterTan nail and three cannulated screws for the treatment of Pauwels III FNFs and investigate the biomechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Rupprecht et al reported that compared with CSs and DHS, InterTan nail was more powerful for treating Pauwels type III femoral neck fractures ( Rupprecht et al, 2011 ). Wang et al conducted a biomechanical comparison of FNS, InterTan nail and three CSs for the treatment of Pauwels III femoral neck fractures ( Wang et al, 2022 ). Based on their results, InterTan nail showed the highest axial stiffness and anteroposterior (AP) bending stiffness, followed by FNS, and then three CSs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rupprecht et al reported that compared with CSs and DHS, InterTan nail was more powerful for treating Pauwels type III femoral neck fractures ( Rupprecht et al, 2011 ). Wang et al conducted a biomechanical comparison of FNS, InterTan nail and three CSs for the treatment of Pauwels III femoral neck fractures ( Wang et al, 2022 ). Based on their results, InterTan nail showed the highest axial stiffness and anteroposterior (AP) bending stiffness, followed by FNS, and then three CSs.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element analysis is a computer simulation method, which has been widely used to study implants for unstable femoral neck fractures ( Peng et al, 2020 ; Zeng et al, 2020 ; Wang et al, 2022 ). It could evaluate the biomechanical properties of different implants by testing the stress and displacement data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main strength of our study is that stress distribution was better in X-PIN+P than DHS or DHS+P and, thus, was apparently superior to implants developed to treat the difficult condition of P3 FNF in young adults. Although we have not compared the X-PIN and X-PIN+P with the more contemporary implants such as the Synthes Femoral Neck System, the Rotationally Stable Screw-Anchor (RoSA) and the InterTan nail, biomechanical studies have shown that both mean axial stiffness and mean torsional stiffness of these implants were comparable to that of the DHS, especially when fractures were stabilized using the sliding hip screw system with a blade [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%